Coexistence of Electrochromism and Bipolar Nonvolatile Memory in a Single Viologen - Parashar R.K.; Kandpal S.; Pal N.; Manna D.; Pal B.N.; Kumar R.; Mondal P.C. (My University, 2025)
Viologens are fascinating redox-active organic compounds that have been widely explored in electrochromic devices (ECDs). However, the combination of electrochromic and resistive random-access memory in a single viologen remains unexplored. We report the coexistence of bistate electrochromic and single-resistor (1R) memory functions in a novel viologen. A high-performance electrochromic function is achieved by combining viologen (BzV2+2PF6) with polythiophene (P3HT), enabling a “push-pull” electronic effect due to the efficient intermolecular charge transfer in response to an applied bias. The ECDs show high coloration efficiency (ca. 1150 ± 10 cm2 C-1), subsecond switching time, good cycle stability (>103 switching cycles), and low-bias operation (±1.5 V). The ECDs require low power for switching the color states (55 μW cm-2 for magenta and 141 μW cm-2 for blue color). The random-access memory devices (p+2-Si/BzV2+2PF6/Al) exhibit distinct low and high resistive states with an ON/OFF ratio of ∼103, bipolar and nonvolatile characteristics that manifest good performances, and “Write”-“Read”-“Erase” (WRE) functions. The charge conduction mechanism of the RRAM device is elucidated by the Poole-Frenkel model where SET and RESET states arise at a low transition voltage (VT = ±1.7 V). Device statistics and performance parameters for both electrochromic and memory devices are compared with the literature data. Our findings on electrochromism and nonvolatile memory originated in the same viologen could boost the development of multifunctional, smart, wearable, flexible, and low-cost optoelectronic devices. © 2023 American Chemical Society.